The precambrian iron-formations in the Limpopo belt as represented by the magnetite quartzite deposits at Moonlight, Koedoesrand area, Northern Transvaal - Badenhorst, Jaco Cornelis (Rhodes University, Faculty of Science, Department of Geology, 1991)
This dissertation is based largely on data that was accumulated during the execution of an exploration program by Iscor Ltd in the Northern Transvaal. The program included geological mapping, geophysical surveys and drilling, on Precambrian iron-formations in the Central Zone of the Limpopo Belt. The structure, stratigraphy, metamorphism, and economic importance of the magnetite quartzites and associated lithologies of the Moonlight prospect are discussed. The lithologies underlying the Moonlight prospect area consist of various pink- and grey-banded gneisses and pink granulite, together with a variety of metasedimentary supracrustal rock-types and concordant serpentinite bodies. The gneissic rock-types consist of chlorite-quartz-feldspar gneiss, chlorite-quartz-feldspar augen gneiss, hornblende-quartz-feldspar gneiss, biotite-quartz-feldspar gneiss, felsic and mafic granulite, and foliated amphibolite. The metasedimentary lithologies are represented by calc-silicates and marble, white quartz-feldspar granulite, magnetite quartzite, metaquartzite and garnet-bearing granulite and gneiss (metapelites). The concordant ultramafic bodies consist of serpentinite with lesser amphibolite, dunite, and chromitite. Intrusive pegmatites and diabase dykes are also present in the prospect area. Metamorphism reached granulite-facies, and more than one retrqgrade metamorphic event is recognized . Amphibolite-facies assemblages are present, but it is uncertain whether they represent another retrograde event . Polyphase deformation has produced intense and complex folding , resulting in irregular magnetite quartzite orebodies. The high metamorphic grades have resulted in medium- grained recrystallization of the magnetite-quartzites with a loss of prominent banding often associated with these rock-types . The magnetite quartzite occurs as three seperate but related ore zones, consisting of one or more ore-bands seperated by other lithologies. All three zones form poor outcrops and suboutcrops in a generally flat lying and sand covered area. Â· Although representing a low-grade iron ore (32% total Fe), the magnetite quartzite deposits at Moonlight are regarded as potentially viable due to the large opencast tonnages available at low stripping ratios, and the relatively cheap and easy beneficiation process needed to produce a magnetite concentrate with 69-70% total Fe.
Keywords: Iron ores -- Geology -- South Africa; Quartzite -- South Africa